The Effect of Pocket Money and Lifestyle On Students Consumer Behavior (Proceeding of the International Conference on Economics, Accounting, and Taxation, 2024)
The purpose of this study is to examine how lifestyle choices and pocket money affect the purchasing habits of Muhammadiyah University of Makassar students enrolled in the Faculty of Economics and Business. Using SPSS software version 26, multiple linear regression is the data analysis technique employed. The research data was obtained through primary data collection using proportional random sampling techniques. According to the study's findings, 1) pocket money significantly affects students' purchasing decisions, with a probability value of 0.000 (less than 0.05) for the pocket money variable. 2) Additionally, lifestyle has a considerable impact on consumer behavior, as seen by its 0.000 probability value (less than 0.05).